Pengaruh Kualitas Pelayanan dan Citra Merek melalui Kepuasan Pelanggan sebagai Variabel Intervening terhadap Loyalitas Pelanggan pada Pelanggan Gojek di Kota Surabaya - Yolla Nanda Tio Erchikka; Rusdi Hidayat (Universitas Batanghari, 2022)
This study intends to find out whether there is an influence on service quality and brand image through customer satisfaction as an intervening variable on customer loyalty to gojek customers in the city of Surabaya. The type of research is quantitative, and the data collection technique is questionnaire method. The population in this study that became the target population was the people of Surabaya who had used the gojek service application. the number of samples used in this was 96 respondents and for representative results, the researchers took 100 respondents. The results of the study indicate that the Quality of Service has a significant effect on customer satisfaction brand image has a significant effect on customer satisfaction. The quality of service has a significant effect on customer loyalty. Brand image has a significant effect on customer loyalty. Customer satisfaction has a significant effect on customer loyalty. The quality of service has a significant effect on loyalty. brand image has a significant effect on loyalty through customer satisfaction.